THE CONNECTION OF COMPOSITION AND GENRE - Sevinch Ikromovna Komilova, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article discusses how Mirkarim Osim provided the unity of form and content in his historical work by creating a harmony between the composition of images, the composition of the narrator's speech, the composition of the plot. The story reflects a similarity between the mythical worldview and the folklore narrative style of Mark Twain's historical novel. However, in terms of the narrative and the novel genre, some differences can be distinguished as both works have their own distinct aesthetic concept.